Teaching public health - Sullivan, Lisa M. (Lisa Marie), 1961-; Galea, Sandro (Johns Hopkins University Press, 2019)
"A comprehensive collection of best practices in public health education. As more students are drawn to public health as a field of study and a profession, bringing varied backgrounds and experiences with them, the number of public health programs and schools of public health has grown substantially. How can teachers meet the changing needs of incoming students--and ensure that graduates have the knowledge, skills, and attributes to pursue further education and forge successful careers in public health? Aimed at experienced and new teachers alike, this timely volume is a cutting-edge primer on teaching public health around the globe. Bringing together leaders in the field with expertise across the educational continuum, the book combines the conceptual underpinnings needed to advance curricula with the resources to train and support faculty in innovative teaching methods."--Publisher